SEEDLESSNESS IN ALOE VERA L. - ROLE OF ENVIRONMENTAL FACTORS IN FAILURE TO HARNESS BENEFITS OF SEXUAL REPRODUCTION - SWATI GUPTA; UMA BHARTI; NAMRATA SHARMA (International Journal of Pharma and Bio Sciences, 2015)
Aloe vera L., is a perennial, evergreen, freely suckering plant, distributed throughout the world and widely recognized for its medicinal and cosmetic values. Species have naturalized well in tropical to sub tropical regions of India. Plants growing in these regions are prolific flower producer but do not set any seed. The flowering period of the species in the subtropical climates of Jammu J & K state, India (area of present study) spans over a period of 6 -7 months (mid October to April). During the peak flowering period (in the months of January and February), the minimum and maximum temperature recorded was quite low and averaged 2.9°C and 26.4°C respectively. Yellowish orange flowers are hermaphrodite and produce a good amount of pollen and ovules both. These are peculiar in showing seasonal variability in pollen viability. Pollen viability is high at the time of initiation and termination of flowering. As the temperature declines, blooming increases, but the pollen viability get decreased. In nature, no pollen germination was ever recorded on the stigmas, although they carried some pollen load. During the flowering period, when the pollen viability was adequate, both manual - self and cross pollinations were carried out. On manual – self pollination, no pollen grain germinated on self – stigma. On manual cross- pollination some pollen germination was recorded (15.38%). Pollen tubes so produced were however inhibited at various levels in the style, revealing some sort of abnormality in pollen tube growth or a stylar inhibition leading ultimately to loss of sexual reproductive output in this plant species.